The labor market impact of Covid-19 on immigrants - Hugh Cassidy (IZA World of Labor, 2022)
The labor market disruptions due to the Covid-19 pandemic and lockdowns impacted immigrant workers more severely than native-born workers in the US, Canada, Australia, and most EU countries. Immigrant workers in most of these countries were more vulnerable to the pandemic since they were more likely to be employed in jobs that are not as easy to perform remotely. The labor market recovery for both groups in the US was rapid, and by Fall 2020, the employment gaps between immigrant and native-born workers, both for men and women, had returned to pre-pandemic levels.
Keywords: J15; J18; J61; J64; 330; immigrants; Covid-19; employment; job remotability